2009
DOI: 10.1055/s-0029-1241205
|View full text |Cite
|
Sign up to set email alerts
|

Fas Ligand (FasL, Apo-1L/CD95L) Expression and Clinical Outcome in Papillary Microcarcinoma and Papillary Thyroid Carcinomas with Diameter Smaller than 1.5 Centimeters

Abstract: This study showed that FasL expression (positivity, staining and intensity) was high and increased in PMC of the thyroid tissue, and above 45 years, in tall cell and oncocytic variants, and in advanced tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The protein encoded by the Fas gene is a member of the TNF-receptor superfamily. This receptor contains a death domain, has been shown to play a central role in the physiological regulation of programmed cell death, and has been implicated in the pathogenesis of various malignancies and diseases of the immune system (37). The present study showed that FasL expression (positivity, staining and intensity) was high and increased in papillary microcarcinoma of the thyroid tissue.…”
Section: Discussionsupporting
confidence: 50%
“…The protein encoded by the Fas gene is a member of the TNF-receptor superfamily. This receptor contains a death domain, has been shown to play a central role in the physiological regulation of programmed cell death, and has been implicated in the pathogenesis of various malignancies and diseases of the immune system (37). The present study showed that FasL expression (positivity, staining and intensity) was high and increased in papillary microcarcinoma of the thyroid tissue.…”
Section: Discussionsupporting
confidence: 50%